Plan de marketing que permita el crecimiento de la práctica del tenis en las escuelas fiscales de la ciudad de Babahoyo - Aguilar García, Aguilar García (2013)
Sport, one of the manifestations of the motor, which from my point of view, is a cognitive involvement, social and emotional drive of great importance, have conflicting views, sometimes encountered and further, in favor of it. In these brief comments I will try to make a thoughtful and critical analysis, perhaps for some and some surprising or inappropriate, but I will compare with others, I hope, my ideas, assumptions and beliefs, rather than my safety, something that I have always doubted...